Mitigation of Antibiotic-Inducted Toxicity in Equine Chondrocytes by Soybean/Glucosamine/Chondroitin Combination - Mochal-King, Cathleen A.; Rashmir, Ann M.; Fortuno, Lowella V.; Grzanna, Mark W.; Au, Angela Y.; Dougherty, Jillian; Frondoza, Carmelita G. (VCOT Open, 2019)
Objectives The aim of this study was to evaluate the effect of amikacin (AK) and enrofloxacin (EF) at concentrations consistent with those obtained by intra-articular and intravenous regional limb perfusion on both cytotoxicity and prostaglandin E2 (PGE2) production by equine chondrocytes. This study also determines if PGE2 production could be reduced by avocado/soybean unsaponifiables (ASU), glucosamine (GLU) and chondroitin sulphate (CS).Study Design Chondrocytes were grown in monolayer from the articular cartilage of 12 horses and treated with clinically relevant concentrations of AK and EF, with or without the combination of ASU + GLU + CS. Positive controls consisted of chondrocytes that were activated with lipopolysaccharide (LPS). Chondrocyte response was evaluated using both MTT cytotoxicity assay and immunoassay for PGE2 production.Results Amikacin and EF generated a dose-dependent cytotoxicity. Amikacin induced 90% cell death at a concentration of 25 mg/mL. Enrofloxacin induced 90% cell death at 1.0 mg/mL and 98% cell death at 10 mg/mL (p < 0.05). Amikacin failed to induce PGE2 production at any of the concentrations studied. In contrast, EF and the positive control (LPS) induced PGE2 production at all concentrations. Induction of PGE2 by EF at all concentrations was significantly reduced (p < 0.05) by pre-treatment with ASU + GLU + CS.Conclusions and Clinical Relevance Horses receiving commonly used dosages of AK and EF may benefit from administration of ASU + GLU + CS.
Keywords: equine; chondrocyte; antibiotic medications; inflammation; PGE2